2023
DOI: 10.1038/s41598-023-32385-y
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling diagnostic object properties for human scene categorization

Abstract: It usually only takes a single glance to categorize our environment into different scene categories (e.g. a kitchen or a highway). Object information has been suggested to play a crucial role in this process, and some proposals even claim that the recognition of a single object can be sufficient to categorize the scene around it. Here, we tested this claim in four behavioural experiments by having participants categorize real-world scene photographs that were reduced to a single, cut-out object. We show that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Furthermore, participants were even more accurate at identifying individual objects in scenes with higher resolutions, suggesting rapid scene categorization cannot be explained by global properties alone, but likely also relies on information provided by individual objects. This finding was extended by Wiesmann and Võ ( 2023 ), who showed that participants were able to successfully identify scenes that were reduced to a single object (e.g., TV, car, bed, etc.) at speeds less than 50 msec.…”
Section: Introductionmentioning
confidence: 60%
“…Furthermore, participants were even more accurate at identifying individual objects in scenes with higher resolutions, suggesting rapid scene categorization cannot be explained by global properties alone, but likely also relies on information provided by individual objects. This finding was extended by Wiesmann and Võ ( 2023 ), who showed that participants were able to successfully identify scenes that were reduced to a single object (e.g., TV, car, bed, etc.) at speeds less than 50 msec.…”
Section: Introductionmentioning
confidence: 60%
“…The relative importance of global properties and object-to-object relations may depend on the type of scene [15]: global properties are particularly informative for outdoor scenes that differ in spatial layout, while objects are more informative for indoor scenes. Systematic transitions between semantically related objects may lead to a higher predictability of eye movements in indoor scenes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Only for indoor scenes, gaze-pointing was more similar to Grad-CAM than spontaneous gaze, and even this was only the case for the Dice scores. Perhaps participants instructed to look at relevant areas might intentionally fixate several objects when categorization depends on object arrangements, even though a single diagnostic object would be sufficient [15]. Moreover, gaze-pointing might lead them to intentionally fixate more diagnostic but less salient objects (e.g., not only fixating the person in an office but also pointing out a printer).…”
Section: Comparison Of the Two Eye Movement Tasksmentioning
confidence: 99%
See 2 more Smart Citations